Estrategias de calidad como instrumento para el desarrollo de la competitividad de las micro y pequeñas empresas de la ciudad de Trujillo - Córtez Vidal, Sandra Elizabeth (2015)
The present research on Quality Strategies as a tool for the development of the competitiveness of micro and small enterprises in the city of Trujillo, is due to the complexity of the market, innovation and greater consumer demands makes present quality strategies to become the foundations for the development of competitiveness. Also Mypes to implement quality strategies are forging their stay in the market, as referring to Mypes companies reflects great importance for the country's economy since 98% of the country's businesses are micro and small enterprises providing over 50% of GDP and are the main generators of employment in the economy. Quality Strategies are present in Mypes company for the development of competitiveness in the context trujillano. Prefer to apply quality strategies to avoid being displaced by competition, build customer loyalty and meet customer requirements. Also keep their customers by friendly service staff. They believe that their customers are loyal and competitive differentiation prefer quality. Keep in mind that the considerations necessary for the development of competitiveness is through product innovation, product differentiation, stay in the market and strengthen abilities and skills. As an alternative for developing a culture of competitiveness and quality policies, continuous improvement and productivity training .It is why taking into account the above considerations Mypes required, proper development of competitiveness will be achieved. Therefore it is concluded that quality strategies favorable impact as a tool for the development of the competitiveness of micro and small enterprises.